Embracing Change in the Modern Working Environment: Exploring the Role of Trust, Experimentation, and Adaptability in the Acceptance of New Technologies - Eva Gößwein; Magnus Liebherr (SAGE Open)
In a working environment facing increasing digitalization and the Fourth Industrial Revolution, the acceptance of new technologies remains an important factor. Based on the Technology Acceptance Model (TAM) and the Artificial Intelligence Acceptance Model (AIAM), this study examines if individual adaptability, trust in technology, as well as openness and willingness to experiment influence technology acceptance in the working environment. Using an online questionnaire approach, a sample of N  = 769 participants ( M  = 51.25, SD  = 13.88 years; 390 female) was recruited to test the theoretically derived model with structural equation modeling. Results suggest including trust in technologies in future technology acceptance models in the working environment. Furthermore, the TAM-variable perceived ease of use was not a significant predictor, which is discussed in detail. Regarding the antecedents derived from AIAM, individual adaptability proves to be relevant, while first insights on the non-significant influence of openness to experiment are gained. The final model explains more than two-thirds of the intention to use new technology and thus provides an important contribution to understanding the acceptance of new technologies in a working environment.